Lone wolf eaudiobook - Picoult, Jodi (Recorded Books Inc., 2012)
A regular at the #1 spot on the New York Times best-seller list, Jodi Picoult crafts stories about family, love, and redemption. Here Picoult tells the tale of Edward Warren, an estranged son who faces a monumental decision when his father is left comatose after a terrible car accident. Edward wants to terminate life support, but his sister Cara wouldn't think of it. As the dilemma tears the family apart, Edward must examine whether his decision is based in mercy, or if he's subconsciously punishing his father for the fight that drove him to leave home years ago.